Non-Newtonian two-phase stratified flow with curved interface through horizontal and inclined pipes - Li, Haiwang (2016)
A model which predicts liquid holdup (ɛTPL), pressure gradient and frictional multiplier (ϕL) for non-Newtonian liquid–gas flow with different interfacial shapes is presented. The interfacial shape is calculated by solving the Young–Laplace equation, while the non-Newtonian liquid is a power-law shear-thinning liquid. The effects of interfacial tension and interfacial shape are included in the model. The results show that the interface shape can be assumed as an arc shape when Bond number is lower than 10. Furthermore the model can predict liquid holdup, two-phase pressure gradient and frictional multiplier for uniform stratified flows. In addition, the result indicate that the interfacial effects on the holdup and pressure difference between two phases are significant, especially for small liquid holdups.